(3fXe GdLeGf aj WHbGJ CUMGH GdfYeGfs - (3EHQGgje Hf eMeO Hf CjOeQ GdYdGFj GdSQGLj, GHf ObeGb , UGQe GdOjf ,J (B809 (3g` s
(3ChdgG (B:s
(3jHJOF HJQLeI GHQGgje Hf COge ef MQa GdgeRI s
(3BNQgG (B:s
(3jfJgi HJQLeI fUQ Hf HTQ Hf Ydi GdYQGbi ef MQa Gdfhf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B50 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B279 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs